A qualitative study on the feasibility of a yoga-based PPI for promoting well-being at a South African HEI - Leana Meiring; René van Eeden; Angelina Wilson Fadiji (SA Journal of Industrial Psychology)
Orientation: An increase in workplace stressors in higher education institutions (HEIs) negatively impacts employees’ mental health and well-being. Workplace wellness promotion programmes that emphasise employee flourishing provide an optimal long-term strategy to improve mental health.